HAL YANG DISUKAI DAN TIDAK DISUKAI PADA KULIAH TATAP MAYA - Nurmida Catherine Sitompul (Jurnal Teknologi Pendidikan, 2023)
Online learning was the safest way to learn during the Covid 19 Pandemic. Virtual lectures are a form of synchronous learning activity where both parties can communicate at the same time even though they don't meet physically. The results of a survey of 383 students found a number of important facts to be considered by teachers in conducting Virtual lectures. The results of this study described the real conditions of the Virtual lectures after 2 semesters, students studied fully online. Virtual Lectures are liked by students because the lecturer explains the subject matter directly and can provide feedback at the same time. These interactions were similar to face-to-face lectures in classrooms before the Covid 19 Pandemic. Virtual Lectures was an Online learning activity where students could confirm the materials and information, they got from the lecturer's presentation needed to convince themselves that what they have understood is in accordance with the learning objectives expected by the teachers. Most of the things that students didn't like about virtual lectures were the class schedules that change frequently or the lecturers who were not consistent with the schedule. Virtual Lectures required a large number of internet quotas so this added to the cost. The quality of the internet network was not good so that the quality of sound or picture reception was not good too, the network is disconnected, the network is thrown out or the connection suddenly turns off, especially when it was raining. Another thing happened to the majority of students who returned to their respective regions. Things that were not liked by these students cause students to feel unable to understand the material presented properly.